An Ethics-based Approach to Global Health Research Part 2: Strategies for Overcoming Logistic and Implementation Challenges - Lukas, Stephanie; Crowe, Susie J.; Law, Miranda; Kahaleh, Abby; Addo-Atuahe, Joyce; Nonyel, Nkem P.; Ombengi, David; Singhal, Mudit; Sultan, Dawood; Tamukong, Robert (Research in Social and Administrative Pharmacy, 2020)
With the growth of global pharmacy partnerships and collaborative research, particularly between high-income countries and low- or middle-income countries, it is necessary to establish best practices for fair and ethical collaboration and research. There is a gap in the pharmacy literature in this regard. Through this commentary, authors will present a pathway for future global health researchers including generating ideas based on mutual needs of the partnership and the community; exploring the importance of regulations including the need to conduct research and partnership projects within the confines of each participant’s professional scope of practice, expertise, and licensure; describing the need to develop agreements and the components that should be included in such an agreement; discussing ethical guidelines for research planning, obtaining ethical approval, and planning for adverse events; and illustrating ethical considerations for research implementation with considerations around consent, data collection, linking patients to care after the completion of the study, and dissemination. Global examples, with a pharmacy- specific approach where applicable, within each section highlight the importance of discussion and action around ethics and equity when pursuing collaborative research, recognizing that many of these situations involve difficult decisions.
Keywords: Global Health Research; Global pharmacy partnerships; Collaborative research